Mucosa associated invariant T and natural killer cells in active and budesonide treated collagenous colitis patients - Daferera, Niki; Nyström, Sofia; Hjortswang, Henrik; Ignatova, Simone; Jenmalm, Maria C.; Ström, Magnus; Münch, Andreas (Frontiers in Immunology, 2022)
Background: Collagenous colitis (CC) is an inflammatory bowel disease, which usually responds to budesonide treatment. Our aim was to study the immunological background of the disease. Methods: Analyses of peripheral and mucosal MAIT (mucosa associated invariant T cells) and NK (natural killer) cells were performed with flow cytometry. Numbers of mucosal cells were calculated using immunohistochemistry. We studied the same patients with active untreated CC (au-CC) and again while in remission on budesonide treatment. Budesonide refractory patients and healthy controls were also included. The memory marker CD45R0 and activation marker CD154 and CD69 were used to further study the cells. Finally B cells, CD4+ and CD8+ T cells were also analysed. Results: The percentages of circulating CD56dimCD16+ NK cells as well as MAIT cells (CD3+TCRVa7.2+CD161+) were decreased in au-CC compared to healthy controls. This difference was not seen in the mucosa; where we instead found increased numbers of mucosal CD4+ T cells and CD8+ T cells in au-CC. Mucosal immune cell numbers were not affected by budesonide treatment. In refractory CC we found increased mucosal numbers of MAIT cells, CD4+ and CD8+ T cells compared to au-CC. Conclusion: Patients with active collagenous colitis have lower percentages of circulating MAIT and NK cells. However, there was no change of these cells in the colonic mucosa. Most mucosal cell populations were increased in budesonide refractory as compared to au-CC patients, particularly the number of MAIT cells. This may indicate that T cell targeting therapy could be an alternative in budesonide refractory CC.